Original paperLichen myxedematosus – diagnostic difficulties. A case report - Jenerowicz, Dorota; Ziembicka, Agnieszka; Piotrowska, Karolina; Neneman, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Lichen myxedematosus (papular mucinosis) comprises the group of conditions associated with deposition of mucin in the skin. Because of considerable variability and complexity of its forms, this rare dermatosis may often cause diagnostic difficulties. New and updated classification of lichen myxedematosus by Rongioletti and Rebora [1] includes 3 variants of the disease: generalized (scleromyxedema), localized and atypical. Lichen myxedematosus is often recognized as a chronic benign condition, however, in its generalized form it may be associated with monoclonal gammopathy (mostly types IgG λ and κ) and its course may be unfavorable for the patient. In the case of lichen myxedematosus both choice and efficacy of the treatment depend significantly on disease variant and the majority of literature reports refer to the treatment with glucocorticosteroids, cytostatic agents, interferon α, plasmapheresis, photoferesis, radiation therapy and PUVA-therapy (including PUVA-bath).